A Novel PowderMEMS Technique for Fabrication of Low-Cost High-Power-Factor Thermoelectric Films and Micro-Patterns - Deng, Kangfa; Zhang, Qihao; Fu, Yangxi; Lasagni, Andres Fabian; Reith, Heiko; Nielsch, Kornelius (Advanced Engineering Materials, 2023)
Thermoelectric (TE) films, which are normally fabricated by MicroElectroMechanical-Systems (MEMS) technology, are crucial for the development of micro-TE devices (e.g., Peltier coolers for hot-spot cooling, TE generators). However, achieving a significant TE property (e.g., high power factor) of TE films and a low-cost fabrication process is challenging. A novel fabrication technique named PowderMEMS to fabricate high-performance, low-cost TE films, and micro-patterns is presented in this article. The TE film is based on agglomeration of micro-sized N-type (Formula presented.) (BTS) powders with stoichiometric composition by the molten binder bismuth (Bi). The influence of the key process parameters (e.g., the weight ratio between the TE powder and the binder, the hot-pressing duration, and pressure) on the TE performance is investigated. The TE film exhibits a maximum power factor of 1.7 (Formula presented.) at room temperature, which is the highest value reported so far for the state-of-the-art TE thick film (thickness > 10 μm). Besides, the PowderMEMS-based TE films are successfully patterned to the micro-pillar array, which opens up a new MEMS-compatible approach for manufacturing micro-TE devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: MEMS integration; powder-based microstructures; PowderMEMS; thermoelectric microstructuring; thermoelectric thin film